USING MEDIA EDUCATION TECHNOLOGIES IN TEACHING STUDENTS-PHILOLOGISTS (Proceedings of Southern Federal University. Philology, 2025)
https://doi.org/10.18522/1995-0640-2025-1-188-193The article presents the problem and its solution in the use of media education and media education technologies for students-philologists who are preparing to become teachers. The purpose of the study is to identify the effectiveness of using media education technologies by students-philologists in the course of mastering literature in the process of educational activities, which contributes to the development of independent creative and critical thinking. The scientific novelty of the study lies in the theoretical and methodological substantiation of this approach in the formation of creative thinking of students-philologists. The practical significance is due to the possibility of applying the obtained results in a literature lesson using the author's methodological recommendations.Key words: media education, media education technologies, media education project, digitalization, media text, students-philologists